(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
In present study it was found that postmortem lividity usually appears 1 to 2 hours after death in punctate and small patchy form, 2 to 4 hours after death in big patchy form and 4 to 6 hours in homogenous form. Fixation of postmortem lividity occured during the period of 7 to 9 hours after death. Lividity is well appreciated in persons with fair complexion and in adequate light (Preferably in day light). Site of lividity helps to determine cause of death in hanging to a certain extent in cases of hanging and drowning by tanking other factors into consideration. Anemia significantly affects the process of appearance, extent and grade of lividity but does not affect fixation of postmortem lividity. In non ambulatory cases lividity appeared early & was well marked after death. It was moderate to well developed and fixed earlier by 2 to 3 hours than in ambulatory cases.